Plastic contamination of the food chain: A threat to human health?. (September 2018) - Waring, R.H.; Harris, R.M.; Mitchell, S.C.
Highlights: A narrative review is presented of the potential toxicity of plastic particles to humans. Nanoparticles are more readily absorbed than microparticles. Atmospheric pollution and ingestion of shellfish are major sources of plastic particles. Toxicity is unlikely unless absorption of plastic particles is high and continuous. Abstract: Macro-plastic pollution is found in terrestrial and marine environments and is degraded to micro-particles (MP) and nano-particles (NP) of plastic. These can enter the human food chain either by inhalation or by ingestion, particularly of shellfish and crustaceans. Absorption across the gastrointestinal tract is relatively low, especially for MPs, which appear to have little toxicity. However, NPs are more readily absorbed and may accumulate in the brain, liver and other tissues in aquatic species and other animals. Studies using nanoparticles of other materials suggest that toxicity could potentially affect the central nervous system and the reproductive system, although this would be unlikely unless exposure levels were very high and absorption was increased by physiological factors.